From widows to warriors : women's stories from the Old Testament - Japinga, Lynn, 1960- (Louisville, Kentucky : WJK, Westminster John Knox Press, 2020)
"In this first of two volumes, Lynn Japinga acquaints us with the women of the Old Testament. This Bible study introduces and retells every female character who contributes to one or more Old Testament stories, diving deeply into what each woman's story means for us today with questions for reflection and discussion"--
The matriarchs -- Women of the exodus -- Women of the promised land -- Women of Israel and Judah -- Women and the prophets -- Other women in the Old Testament
Includes bibliographical references (pages 183-201) and indexes.
Keywords: Women in the Bible; Bible. -- Biography; Bible; Women in the Bible; Biographies